2014
DOI: 10.1128/aac.02406-14
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Drug Resistance-Mediating Plasmodium falciparum Genetic Polymorphisms by Seasonal Malaria Chemoprevention in Burkina Faso

Abstract: e Seasonal malaria chemoprevention (SMC), with regular use of amodiaquine plus sulfadoxine-pyrimethamine (AQ/SP) during the transmission season, is now a standard malaria control measure in the Sahel subregion of Africa. Another strategy under study is SMC with dihydroartemisinin plus piperaquine (DP). Plasmodium falciparum single nucleotide polymorphisms (SNPs) in P. falciparum crt (pfcrt), pfmdr1, pfdhfr, and pfdhps are associated with decreased response to aminoquinoline and antifolate antimalarials and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
52
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 39 publications
6
52
3
Order By: Relevance
“…Piperaquine is a related bisaminoquinoline, but mechanisms of resistance are uncertain, and studies of the selective pressure exerted by DP have yielded conflicting results. Specifically, use of DP for treatment (24) or chemoprevention (25) did not select for the polymorphisms associated with aminoquinoline resistance in Burkina Faso, but in Uganda, recent treatment with DP selected for the pfmdr1 86Y and 1246Y mutations (26). Our new results shed additional light on this area.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Piperaquine is a related bisaminoquinoline, but mechanisms of resistance are uncertain, and studies of the selective pressure exerted by DP have yielded conflicting results. Specifically, use of DP for treatment (24) or chemoprevention (25) did not select for the polymorphisms associated with aminoquinoline resistance in Burkina Faso, but in Uganda, recent treatment with DP selected for the pfmdr1 86Y and 1246Y mutations (26). Our new results shed additional light on this area.…”
Section: Discussionmentioning
confidence: 82%
“…The differing results may have been due to the changing baseline of polymorphism prevalence in Uganda, with decreasing prevalence of pfmdr1 1246Y and pfcrt 76T over time. Differences in results between West and East Africa may also be explained by differences in parasite backgrounds; of note, the pfmdr1 1246Y mutation, which until recently was widespread in Uganda, has consistently been uncommon in Burkina Faso (24,25,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When isolates from the first incident malaria cases were typed, the triple dhfr mutation and the dhps g437 mutation were more frequent in children who received SPAQ than in the malaria cases in the DHAPQ group and in the control group, but the frequencies of pfcrt CVIET T76, pfmdr1 Y86, and pfmdr1 Y184, associated with resistance to AQ, were similar in all three groups. Analysis of molecular markers of resistance in a subset of samples from children in this study taken at enrollment and at the end of the transmission season have been reported separately (28). Among children who received SPAQ who had parasitemia at the end of the transmission season, the frequency of pfcrt 76T, pfdhfr 59R, and pfdhfr 108N was greater than at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Due to structural similarities between PPQ and CQ, there have been attempts to identify common markers of resistance (9,10). However, the limited number of studies available did not observe selection of Pfcrt single nucleotide polymorphisms (SNPs) (11,12).…”
mentioning
confidence: 99%